2010
DOI: 10.1155/2010/968960
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐Year Retrospective Review of Salmonella Infections at the Children’s Hospital in London, Ontario

Abstract: A wider knowledge of the epidemiological risk factors for Salmonella infection may improve diagnosis. Higher admission rates were expected in children younger than 12 weeks of age, those recently treated with antibiotics and those who had a significant underlying medical condition. A prospective, multicentre study is needed to further address questions regarding increased illness severity and appropriate management of Salmonella infections in children younger than 12 weeks of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
2
10
1
1
Order By: Relevance
“…Almost all the isolates recovered from animals and sewage wastes were considered as other Salmonella serotypes because only three important serotypes namely Salmonella Enteritidis, Salmonella Typhimurium and Salmonella Typhi were detected by multiplex PCR employed in the present study. These results are in partial agreement with other authors wherein besides Salmonella Enteritidis and Salmonella Typhimurium, other Salmonella serotypes have also been identified in animals and sewage waste [ 22 , 23 ]. Further, in our study bovine and equine samples failed to yield Salmonella isolates, although earlier studies [ 24 , 25 ] have revealed a higher incidence of Salmonella spp.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Almost all the isolates recovered from animals and sewage wastes were considered as other Salmonella serotypes because only three important serotypes namely Salmonella Enteritidis, Salmonella Typhimurium and Salmonella Typhi were detected by multiplex PCR employed in the present study. These results are in partial agreement with other authors wherein besides Salmonella Enteritidis and Salmonella Typhimurium, other Salmonella serotypes have also been identified in animals and sewage waste [ 22 , 23 ]. Further, in our study bovine and equine samples failed to yield Salmonella isolates, although earlier studies [ 24 , 25 ] have revealed a higher incidence of Salmonella spp.…”
Section: Discussionsupporting
confidence: 93%
“…Beside this, in the present study, the serotypes namely Salmonella Enteritidis and Salmonella Typhimurium were identified from human infants and fresh vegetables. Similar serotype isolation/identification of Salmonella Enteritidis and Salmonella Typhimurium has also been reported by several authors from human infants and vegetables [ 21 , 22 ]. Almost all the isolates recovered from animals and sewage wastes were considered as other Salmonella serotypes because only three important serotypes namely Salmonella Enteritidis, Salmonella Typhimurium and Salmonella Typhi were detected by multiplex PCR employed in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies identified several risk factors for S . Enteritidis infections for this age group, including international travel [51,52], riding in shopping carts and exposure to raw meat and poultry products [53], and contact with reptiles [43,52,54] and cats [43]. In our study, adults 60 years of age and older had the lowest IRR among all age groups, which is in contrast with other studies [29,55].…”
Section: Discussioncontrasting
confidence: 82%
“…This serovar has not been isolated so far from animals or humans in Grenada. However, it has been reported as a cause of clinical salmonellosis with positive blood cultures in children at the Children's Hospital, London, Ontario, Canada (Cellucci et al 2010), and has been implicated in human infection from feral pigeons. It also has been isolated from beef samples in Morocco and from faecal samples of kangaroos in Australia (Haag-Wackernagel & Moch 2004;Bouchrif et al 2009;Potter et al 2011).…”
Section: Discussionmentioning
confidence: 99%